Income Inequality and Economic Freedom: The 2000s - Yılmaz, Ilkay; Balkan, Mehmet Murat; Tağ, Mehmet Nasih (Journal of Applied And Theoretical Social Sciences, 2022)
This study examines the relationship between income inequality and economic freedom by using two concepts developed in institutional economics, namely “extractive and inclusive institutions”. We argue that income inequality might be high both in countries with extractive institutions, where the level of economic freedom is low, and in countries with inclusive institutions, where the level of economic freedom is high. We propose a U-shaped relationship between income inequality and economic freedom. We use a panel data set containing 1425 country-year observations from 137 countries for the years from 2000 to 2018 to test our proposition. The results confirm our expectation that the relationship between income inequality and economic freedom is negative at low levels of economic freedom, but positive at high levels of economic freedom.